How and Why the Land Resources Changed: A Chronological Change of Land Use and Land Cover in Sri Lanka - Manawadu, L.; Gunathilaka, M.D.K.L.; Wijeratne, V.P.I.S.; Gunathilake, K.L.W.I. (IGI Global, 2021)
Human activities have recognized in recent years as the most significant force shaping the biosphere. This is completely true concerning rapid changes in the land surface. Concerning land resources, it is important to understand how this change happens. Thus, this chapter aims to review how this change has occurred throughout the history of Sri Lanka. A piecemeal approach in the unsustainable manner of land resource utilization towards severe land changes illustrates and compares the land use and land cover changes in significant phases in the history of Sri Lanka. This was further revitalized as well as influenced by the land-use policies introduced throughout history. The absence of a clearly defined land-use policy in the country after independence is problematic when addressing land-related issues. Consequently, chronological changes in land use and land cover existed within the country has now doubled and more intensified than ever.